2017
DOI: 10.1007/s13346-017-0413-4
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to prevent bleeding associated with anticoagulants: current status and recent developments

Abstract: Anticoagulants are widely used for the prophylaxis and treatment of cardiovascular disorders and to prevent blood clotting during surgeries. However, the major limitation associated with anticoagulant therapy is bleeding; all the current anticoagulants do have a bleeding risk. The propensity to bleed is much higher among the elderly population and patients with renal insufficiency. Therefore, there is an utmost and urgent clinical need for a highly efficient, nontoxic antidote with excellent anticoagulant reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 99 publications
0
25
0
12
Order By: Relevance
“…Most of the research on protamine neutralization of UFHs is based on clinical cases of patients undergoing procedures involving heparinization or in vitro and ex vivo assessments of their anticoagulant activities after the neutralization reactions . It has already been demonstrated that the anticoagulant activity of HPI is neutralized more effectively than that of HBI ; however, the chemical aspects leading to these different neutralization profiles have not been clearly elucidated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research on protamine neutralization of UFHs is based on clinical cases of patients undergoing procedures involving heparinization or in vitro and ex vivo assessments of their anticoagulant activities after the neutralization reactions . It has already been demonstrated that the anticoagulant activity of HPI is neutralized more effectively than that of HBI ; however, the chemical aspects leading to these different neutralization profiles have not been clearly elucidated so far.…”
Section: Introductionmentioning
confidence: 99%
“…NOACs are no longer “novel” but their reversal agents definitely are. DOAC reversal agents at a glance [Table 3][17181920212223242526272829] and a summary of 16 human in vivo clinical trials involving specific and non-specific DOAC reversal agents[3031323334353637383940414243444546] [Table 4] are presented here for ready referral.…”
Section: Introductionmentioning
confidence: 99%
“…Early administration of activated charcoal can hamper absorption of DOACs from the gutand can be followed by charcoal filtration. [26] Haemodialysis is partially successful in removing Dabigatrin from the circulation, but is ineffective for anti-Factor Xa DOACs whereas therapeutic plasma exchange maybe employed for urgent rivaroxaban reversal. [2627] Intermittent haemodialysis reduced dabigatran concentrations by 52%-77% but a rebound reaching 87% within 120 minutes post dialysis was observed in a case series of five patients[28] Recombinant activated factor VII can also be empirically used.…”
Section: Introductionmentioning
confidence: 99%
“…5 This has initiated diverse attempts to develop safer heparin antidotes, such as cationic polymers and small molecules, which all largely rely on the electrostatic binding with heparin. [6][7][8][9][10][11][12] Although efficient binding can be achieved, cationic platforms often lack specificity to heparin and usually exhibit high cytotoxicity. Furthermore, the complexes formed with heparin are often large and ill-defined aggregates.…”
mentioning
confidence: 99%